Family Structure and Delinquency in the English-Speaking Caribbean: The Moderating Role of Parental Attachment, Supervision, and Commitment to Negative Peers - Freemon, Kayla (Youth violence and juvenile justice, 2023)
Growing up in a household without two parents present is an established risk factor for youth delinquency. However, much of the research on family structure and delinquency derives from U.S. samples, limiting applicability to the developing world. The present study explores the role of traditional and non-traditional family structures on self-reported delinquency in eight English-speaking Caribbean nations. We further examine the moderating role of family processes (parental attachment and parental supervision) and commitment to negative peers on this relationship. We find that youth from intact nuclear families, with a mother and father present, engage in less delinquency than youth from intact blended, single-parent, or no-parent households. Further, family structure moderated the relationship between delinquency, parental attachment, and commitment to negative peers. Theoretical and research implications are discussed.